2021
DOI: 10.3389/fimmu.2020.599771
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuronal Pentraxins as Synaptic Binding Partners of C1q and the Involvement of NP1 in Synaptic Pruning in Adult Mice

Abstract: Elements of the immune system particularly that of innate immunity, play important roles beyond their traditional tasks in host defense, including manifold roles in the nervous system. Complement-mediated synaptic pruning is essential in the developing and healthy functioning brain and becomes aberrant in neurodegenerative disorders. C1q, component of the classical complement pathway, plays a central role in tagging synapses for elimination; however, the underlying molecular mechanisms and interaction partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 76 publications
1
37
0
Order By: Relevance
“…3b-4). The recently described role of NPTX1 in synaptic pruning, by activation of the complement-microglia axis, could be intensified upon neurodegeneration (Kovács et al 2020) (Fig. 3b-5).…”
Section: Neuronal Pentraxins In Synaptic Dysfunction and Neurodegeneration: A Proposed Mechanismmentioning
confidence: 82%
See 3 more Smart Citations
“…3b-4). The recently described role of NPTX1 in synaptic pruning, by activation of the complement-microglia axis, could be intensified upon neurodegeneration (Kovács et al 2020) (Fig. 3b-5).…”
Section: Neuronal Pentraxins In Synaptic Dysfunction and Neurodegeneration: A Proposed Mechanismmentioning
confidence: 82%
“…Moreover, there is evidence that NPTXs are involved in intracellular processes such as mitochondrial dynamics and trafficking, and neuronal apoptosis (Clayton et al 2012;Rahim et al 2013;Tseng and Bixby 2011). In addition, recent studies concluded a role of NPTXs in synaptic pruning by activation of the classical complement cascade (Kovács et al 2020) (Fig. 3a).…”
Section: Role Of Neuronal Pentraxins In Synaptic Function and Plasticitymentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, the expression of genes encoding other components of the complement cascade ( C3), complement receptors (Itgam, Itgax, Itgb2 ), of. neuronal proteins that mediate the synaptic deposition of C1q ( Nptx1, Nptx2) (35) and of Trem2 , a microglial receptor involved in synapse removal (36) was unchanged (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 99%